Celso Furtado and development: foundation and foresight - Candido Mendes; André Villalobos (Dados: Revista de Ciências Sociais, 2006)
The article analyzes the political and intellectual career of Brazilian economist Celso Furtado, who passed away in November 2004. The author highlights Furtado's decisive role in the construction of relevant public institutions for the country and his original reflections on Brazilian economic thinking and the issue of development.